Pelatihan Penulisan Artikel Jurnal untuk Jurnal Fakultas Ilmu Sosial Universitas Negeri Semarang - Apik Budi S; Wasino Wasino; Syaiful Amin; Tsabit Azinar (Universitas Negeri Semarang, 2019)
In addition to have an important meaning for the college, where the journal is also important for teachers who take shelter in it. For teachers, existence junal can be used as a medium to pour a wide variety of knowledge, ranging from the idea of ​​thinking, nor Mr studies. Various kinds of knowledge that will provide many benefits to the public, both for the world of education mapun general public. It is important for faculty to continue to improve their knowledge and their ability to write journal articles.Faculty of Social Sciences, State University of Semarang (Unnes) has had five journals: the Journal of Paramitha, Community Journal, Journal of Social Science Forum, Integralistic Journal, and the Journal of Geography. The fifth journal has been going well. Participation of lecturers in writing in these journals are also high. But the existence of these journals are still to be supported by an increase in the quality and quantity of publications in journals, so the usefulness of the journal for the higher audiences. One way to increase the quality and quantity that can be achieved is by training writing journal articles for lecturers in the FIS Unnes.